Żołnierze-górnicy z powiatów elbląskiego i braniewskiego (1949–1959) - Burczyk, Dariusz (Pamięć i Sprawiedliwość, 2012)
The presented work tells about soldiers from Elbląg and Braniewo districts, directed to do their military service in coal and uranium mines, and in quarries. The geographical framework of the study was determined by the territorial competence of the Military Draft Offi ce (WKU) in Elbląg, the army records of which have been analysed for the needs of this article. In addition to general fi ndings, the author has managed to determine the names of 483 persons, inhabitants of Elbląg and Braniewo districts (then part of the Gdańsk voivodeship), directed to work in coal and uranium mines, and quarries. The fi rst four Labour Battalions were established on 15 October 1949. In the following years more were created, as result of which by the end of 1953 already 26,000 soldiers were working in the mining sector, grouped in 26 battalions. “The soldiers with pickaxes” were not authorised to carry weapons, nor to be promoted to suboffi cials; directed to torturous work 10–12 hours a day, soldiers-miners payed the price of their service in the army with loss of health, often even life. Of 200,000 recruits directed in the years 1949–1959 to work in mines, today only about 40,000 are still alive, and of 2870 soldiers sent to the uranium mine at Kowary near Jelenia Góra, only 200. As result of the dissolution in 1955 of the organisation “Service to Poland” (“Służba Polsce”) its subordinated units of Alternative Military Service (labour battalions) were transformed into the Military Mining Corps (WKG), from then on subordinated to the minister of mining. In total, soldiers of labour battalions (military mining battalions) were employed in 60 mines in Lower and Upper Silesia, and western Lesser Poland. In its peak (1956) the WKG was composed of ca 35,000 soldiers. The gradual process of abolishing military mining battalions began in autumn 1956 and was completed in 1959. Soldiers-miners from Elbląg and Braniewo districts were mainly persons aged 20–21, from working class and peasant families, graduated from 4 or 7 classes of elementary school. A good part of them – 93 – had criminal records. The list stated at the end of the article contains personal data of all persons subjected to universal compulsory military service, residents of Elbląg and Braniewo districts in the years 1949–1959, of whom documentation certifying their service in coal, uranium mines or quarries is preserved. The article also includes an annex stating a complete List of battalions, the soldiers of which worked in coal mines, uranium mines and quarries in the years 1949–1959.